Analisis Hubungan CAR dan SIZE Terhadap FDR dan Pengaruhnya Terhadap Kinerja Perbankan Syariah di Indonesia - Yeni Hartini Herawati; Leni Nur Pratiwi; Iwan Setiawan (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to determine the effect of the CAR and Firm Size variables on bank liquidity as measured by ROA and determine the effect of FDR on the financial performance of Islamic banks as measured by ROA in Islamic banking in Indonesia for the 2015-2019 period. In this study, the data sample used was selected through a purposive sampling method with data taken from secondary data, namely the annual report of Islamic banks for the 2015-2019 period and the sample in this study used 11 Islamic Commercial Banks. This study uses the method of Descriptive Analysis and Path Analysis using the Eviews 9 and WarpPLS 7.0 applications as analytical tools. The results of this study are CAR has no effect on FDR, Firm Size has a negative and significant effect on FDR and FDR has a positive and significant effect on ROA.